Bibliometric Analysis of Gender Authorship Trends and Collaboration Dynamics Over 30 Years of Spine 1985 to 2015. Issue 14 (15th July 2018) - Brinker, Alexander R.; Liao, Jane L.; Kraus, Kent R.; Young, Jocelyn; Sandelski, Morgan; Mikesell, Carter; Robinson, Daniel; Adjei, Michael; Lunsford, Shatoria D.; Fischer, James; Kacena, Melissa A.; Whipple, Elizabeth C.; et al.
Abstract : Study Design: A bibliometric analysis. Objective: The aim of this article was to study bibliometric changes over the last 30 years of Spine . These trends are important regarding academic publication productivity. Summary of Background Data: Inflation in authorship number and other bibliometric variables has been described in the scientific literature. The issue of author gender is taking on increasing importance, as efforts are being made to close the gender gap. Methods: From 1985 to 2015, 10-year incremental data for several bibliometric variables were collected, including author gender. Standard bivariate statistical analyses were performed. Trends over time were assessed by the Cochran linear trend. A P  < 0.05 was considered statistically significant. Results: Inclusion criteria were met for 1566 manuscripts. The majority of the manuscripts were from North America (51.2%), Europe (25.2%), and Asia (20.8%). The number of manuscripts, authors, countries, pages, and references all increased from 1985 to 2015. There was a slight increase in female first authors over time (17.5% to 18.4%, P  = 0.048). There was no gender change over time for corresponding authors (14.3% to 14.0%, P  = 0.29). There was an 88% increase in the percentage of female first authors having male corresponding authors ( P  = 0.00004), and a 123% increase in male first authors having female corresponding authors ( P  = 0.0002). The 14% to 18% of female authors in Spine is higher than the ∼5% female membership of the Scoliosis Research Society and North American Spine Society. Conclusion: Manuscripts in Spine over the past 30 years have shown a significant increase in the number of authors, collaborating institutions and countries, printed pages, references, and number of times each manuscript was cited. There has been a mild increase in female first authorship, but none in corresponding authorship. Increases in female authorship will likely require recruitment of more females into the discipline rather than providing females in the discipline with authorship opportunities. Level of Evidence: N/A